The Effectiveness of Outdoor Learning Method to Improve Students’ English-Speaking Skills at SMAN 7 Bulukumba - Mawaddah, Safira; Noni, Nurdin; Korompot, Chairil Anwar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
The research aims to find out whether or not the outdoor learning method is effective in improving students’ English-speaking skills. The researcher applied the pre-experimental method, and to achieve the research objectives, data collection was conducted through a pre-test and a post-test. The population of this study is all of the year 10th of SMAN 7 Bulukumba students, and the sample of this study consisted of 35 students of class X.1 in that school was recruited with the cluster random sampling technique. After being analyzed with a T-Test, the results of the pre-test and post-test of students’ English-speaking skills through the outdoor learning method indicate that the probability value, which is 0.001, was significantly lower than the level of significance (0.05). Therefore, the alternative hypothesis (H1) was accepted, and after being analyzed with the N-Gain value, the results showed that the improvement that occurred in the speaking skills of the sample group was low. This implies that the outdoor learning method may need to be combined with other strategies to achieve better results, especially in improving students' speaking, and this method will be taken into consideration for teachers in designing more interesting and interactive learning activities. Therefore, it can be concluded that outdoor learning is effective in improving students' English-speaking skills.